"In The Spirit" - A. Santoso (Acta Theologica)
The Ecumenical and Reformed Creeds and Confessions hold a continuity of Trinitarian doctrine as formulated since the Nicene creed (325 AD). Yet the role of the spirit seems to be undermined in such formulations. The historical context of the Nicene creed emphasized on the homoousios of the Son. Thus, the filioque in the Nicene later formulation. In this article, the author addresses the lacuna of the role of the Spirit in the traditional Trinitarian formulations. Based on John Calvin’s understanding of an autotheos Trinity, and his timeless view of eternity, the significance of the Spirit should have an equally prominent role. The renewed position should leave no ontological subordinationism either of the Son or the Spirit—a correction to the Eastern and the Western church formulations. In addition, the reformulation read in autothean interpretation shows how the inherent hypostasis submission fits with God’s mission in the history of salvation.